2007
DOI: 10.1515/ijamh.2007.19.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HIV risk perception, condom use and sexual history among Jamaican youth, 1996-2004

Abstract: As the number of HIV/AIDS cases continues to increase among youth, aged 15-24 years, it becomes critically important to identify the factors that are contributing to this increase. Trends in perceived risk and risk behaviours were examined among youth by sex and age in an attempt to address this concern. National-level cross-sectional data across three time periods (1996, 2000, 2004) gathered from youths, aged 15-24 years in Jamaica for six outcomes were examined (perceived risk, ever had sex, initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Additionally, research conducted by Siu and colleagues among men in Uganda also revealed that aspects of masculinity pertaining to reputation undermine uptake of HIV testing and treatment services. 36 The need to include 'masculinity' in HIV prevention programs to reduce men's vulnerability to HIV acquisition has been highlighted in studies conducted in the United States [37][38][39][40] and in developing countries such as Brazil, India 33 and Mozambique. 9 Over 50% of the men in our study reported having multiple sexual partners within the past 12 months, which is considerably higher than what has been reported in other high-risk settings, such as sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, research conducted by Siu and colleagues among men in Uganda also revealed that aspects of masculinity pertaining to reputation undermine uptake of HIV testing and treatment services. 36 The need to include 'masculinity' in HIV prevention programs to reduce men's vulnerability to HIV acquisition has been highlighted in studies conducted in the United States [37][38][39][40] and in developing countries such as Brazil, India 33 and Mozambique. 9 Over 50% of the men in our study reported having multiple sexual partners within the past 12 months, which is considerably higher than what has been reported in other high-risk settings, such as sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…46 The need for development and implementation of culturally relevant interventions to reduce risk behaviours among Jamaica's youth has been documented in other studies. 8,12,38,44 Although attitudes towards gender norms are changeable, 15 it is likely to be a challenging and gradual process, which ideally should be addressed early in life. 33 Modifiable social and cultural behaviours are central to reducing HIV transmission, especially in this resource-poor setting, given that there is still no vaccine and treatment is costly.…”
Section: Discussionmentioning
confidence: 99%
“…For the 30% of the population in the English-speaking Caribbean who are adolescents and youth, sexual development occurs against a backdrop of regional instability and numerous challenges to health and development. Approximately one-third of adolescents in this region have had sexual intercourse, with many debuting at early ages; on average, boys at age 11 and girls at ages 14 -15 [1][2][3][4][5][6][7]. Moreover, studies report that among adolescents who are sexually active, one-third have had multiple sexual partners in the past year, 90% have used condoms, but only 16%-25% have used them consistently, and approximately half of those who are sexually active reported that their first sexual intercourse was forced [1][2][3].…”
mentioning
confidence: 99%
“…Similarly, Collins et al (2000) (Hoffman et al, 2011;Norman, Figueroa, Wedderburn, Byfield, Bourne, & Gebre, 2007). For example, Norman et al (2007) used data from a national-level reproductive health survey across three time periods (1996,2000,2004) among Jamaican male and female youth (ages 15 -24 years) to examine sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Norman et al (2007) used data from a national-level reproductive health survey across three time periods (1996,2000,2004) among Jamaican male and female youth (ages 15 -24 years) to examine sexual behavior.…”
Section: Discussionmentioning
confidence: 99%